Intercellular transmission of alpha-synuclein - Wu, Shenjie; Schekman, Randy W. (Frontiers in Molecular Neuroscience, 2024)
An emerging theme in Parkinson’s disease (PD) is the propagation of α-synuclein pathology as the disease progresses. Research involving the injection of preformed α-synuclein fibrils (PFFs) in animal models has recapitulated the pathological spread observed in PD patients. At the cellular and molecular levels, this intercellular spread requires the translocation of α-synuclein across various membrane barriers. Recent studies have identified subcellular organelles and protein machineries that facilitate these processes. In this review, we discuss the proposed pathways for α-synuclein intercellular transmission, including unconventional secretion, receptor-mediated uptake, endosome escape and nanotube-mediated transfer. In addition, we advocate for a rigorous examination of the evidence for the localization of α-synuclein in extracellular vesicles.